Tourism Clustering in Russia and Abroad - Aleksandrova, Anna Y. (Turyzm/Tourism, 2007)
The world travel industry is now at the stage of production modernization and clustering. A comparative analysis of tourism clustering in the United States, South Africa, New Zealand, Sri Lanka, Jamaica, Macedonia and Russia indicates that tourism clusters have become a global phenomenon.